Encyclical Laudato si’ on the Question of Progress - Kania, Witold (Studia Ecologiae et Bioethicae, 2020)
Progress is one of the most recognizable characteristics of modern times. The present paper addresses the question of progress as the underlying theme of the encyclical Laudato si'. Progress has both good and bad sides. The latter are expressed in terms that have a fundamental significance to the encyclical, such as, “irrational faith in progress” and “the myth of unlimited material progress”. In order to gain a clearer understanding of those terms, the author begins with outlining the history of the idea of progress and the philosophical criterion for its assessment. Then, he provides a critical analysis of the technocratic paradigm embodying the false face of progress. Within this framework, progress is presented as imperative and unlimited. However, by placing man in the centre and reducing his purpose in life to a relativistic principle “use and throw away”, it leads to a global ecological, spiritual and cultural crisis. The following part of the paper is devoted to a new model of progress proposed by Pope Francis. This type of progress has both a vertical and horizontal dimension. Embedded in the Holy Trinity, it reaches its peak in Jesus Christ and it promotes human life and protects the work of creation. Its fruit is to be individual concern for the poor and greater justice between nations. It cannot be achieved without changing the mentality (conversion) and specific individual and political decisions. The last part of the article answers the question about the novelty of the model of progress proposed by Pope Francis.